L1 Transfer / L1 Interference in Students’ Academic Writing (Practice). (Eurasian Journal of Philology Science and Education, 2015)
This study aims to analyze errors in academic writing practices by Central Asian, university students enrolled in advanced English for Academic Purposes course focusing on research writing and reading.Research essays written by 40 first-and second-year students were initially analyzed to categorize the typical errors as a result of Russian language interference/transfer. Russian was assumed to be the firstlanguage (L1) in the present research due to the fact that it was named as the language most frequently utilized by respondents both individually and in their families. The researchers explored the way thatmultilingual speakers of languages that share certain similar syntactic structures (e.g., Kazakh and Russian) demonstrate language interference and transfer. Learners demonstrated transfer/interferencein areas like grammar structures (construction of sentences, participles and cases), prepositions and collocations to name a few. The theoretical framework underpinning this study was outlined and discussed in a separate article.
Keywords: Second language writing; second language acquisition; English language education; English in higher education